2015
DOI: 10.14814/phy2.12381
|View full text |Cite
|
Sign up to set email alerts
|

Subdiaphragmatic vagus nerve activity and hepatic venous glucose are differentially regulated by the central actions of insulin in Wistar and SHR

Abstract: Glucose is the most important energy substrate for the maintenance of tissues function. The liver plays an essential role in the control of glucose production, since it is able to synthesize, store, and release glucose into the circulation under different situations. Hormones like insulin and catecholamines influence hepatic glucose production (HGP), but little is known about the role of the central actions of physiological doses of insulin in modulating HGP via the autonomic nervous system in nonanesthetized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
0
14
0
2
Order By: Relevance
“…The rats were implanted with unilateral guide cannula (21 gauges) for ICV injections of drugs, which was described previously [ 35 , 36 ]. Coordinates for lateral ventricle injections (−1.0 mm to Bregma; 1.5 mm lateral to midline; and −4.5 mm to the surface of the skull) were based on the rat atlas of Paxinos and Watson [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The rats were implanted with unilateral guide cannula (21 gauges) for ICV injections of drugs, which was described previously [ 35 , 36 ]. Coordinates for lateral ventricle injections (−1.0 mm to Bregma; 1.5 mm lateral to midline; and −4.5 mm to the surface of the skull) were based on the rat atlas of Paxinos and Watson [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hormones such as insulin and catecholamines influence PHG but little is known about the physiological centrally acting insulin doses in modulating PHG through SNA rats unanesthetized especially in SHR has the characteristic of insulin resistance among other metabolic disorders. Previous studies from our laboratory showed a 27% decrease in blood glucose measured directly into the hepatic vein (CGVH) Wistar rats already at 10 minutes after insulin ICV injection (100 nU / ml) without significant changes (3%) in SHR ( Ribeiro et al, 2015). The pre-treatment with atropine methyl-CGVH completely blocked the reduction, whereas pretreatment with propranolol and phentolamine induced a decrease of 8% by CGVH insulin after ICV injection in Wistar rats.…”
Section: Introductionmentioning
confidence: 81%
“…Hormônios como insulina e catecolaminas influenciam a PHG mas pouco se conhece acerca da ação central de doses fisiológicas de insulina na modulação da PHG através do SNA em ratos não anestesiados especialmente em SHR que tem como característica resistência à insulina dentre outras disfunções metabólicas. Estudos anteriores do nosso laboratório mostraram uma diminuição de 27% na glicemia medida diretamente na veia hepática (CGVH) de ratos Wistar já ao 10 minutos após a injeção ICV de insulina (100 nU /mL) sem alterações significantes (3%) em SHR (Ribeiro et al, 2015). O pré-tratamento com metil-atropina bloqueou totalmente a redução CGVH, enquanto que o pré-tratamento com propranolol e fentolamina induziu uma diminuição de 8% em CGVH após injeção ICV de insulina em ratos Wistar.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In the liver, efferent activation of the vagus nerve promotes the formation of glycogen by activating glycogen synthetase (48). Parasympathetic innervation of the liver also reduces hepatic glucose release (41). These two mechanisms can function to reduce glucose concentrations in the blood.…”
Section: List Of Figuresmentioning
confidence: 99%